A bioelectronic system for insulin release triggered by ketone body mimicking diabetic ketoacidosis in vitro1. Issue 36 (4th May 2015) - Gamella, Maria; Guz, Nataliia; Pingarrón, José M.; Aslebagh, Roshanak; Darie, Costel C.; Katz, Evgeny
<x xml:space="preserve">Abstract</x> A bioelectronic system was activated with a biomarker of diabetic ketoacidosis to release insulin operating as a Sense-and-Act device.